Motivasi Belajar Matematika Siswa Kelas VIII SMP Negeri 7 Rambah Hilir Pada Pembelajaran Daring Selama Masa Pandemi Covid-19 - Wahyuni, Tri Sari; Isharyadi, Ratri; Arcat, Arcat (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2021)
This study aims to describe the motivation of learning mathematics experienced by students in online learning during the covid 19 pandemics. This research uses a descriptive quantitative approach. The research was conducted at SMP Negeri 7 Rambah Hilir involving 34 students. Data collection techniques in this study through filling out questionnaires. The results of this study showed that the motivation to learn mathematics students analyzed was an average intrinsic indicator with an average of 73,67% good categories, extrinsic indicators with an average of 67,21% good categories, curiosity with an average of 59,80% good categories, independence with an average of 69,21% good categories, and readiness with an average of 72,34% good categories. The average overall motivational indicator for learning mathematics in grade VIII of SMP Negeri 7 Rambah Hilir in online learning during the covid 19 pandemic was as low as 68,44 % in the good category. However, there are still things that need to be improved to improve the overall.